Política antitruste e regulação da concorrência no Brasil: um estudo sobre o setor de telecomunicações - Teixeira, Henrique de Andrade (2011)
Antitrust authorities and regulatory agencies address competition issues in regulated markets and in this way both may present conflicting and harmonious opinions. Therefore, the application of antitrust policy in regulated markets in Brazil is an interesting object of investigation. Within competitive context, the telecommunications is the industry with the largest presence of these authorities, chiefly within mergers between companies in this sector. Moreover, constant technological innovations and the phenomenon of convergence of technology and services give the telecommunications industry very specific characteristics. Thus, this study intends to examine the application of antitrust policy in the telecommunications industry in Brazil. For this purpose, the study evaluated the performance of the regulator and the antitrust authority in antitrust proceedings within mergers occurring since the installation of the current regulatory framework, between the years 1998 to 2010. Analyses were performed primarily from two perspectives. First, if the understandings of both authorities were in-line with the current reality of the industry, and second, if the rulings of both the antitrust authority and the regulatory agency were consistent. The conclusion is that the understandings still retain certain applicability to current industry realities. There remains a risk, however, of the rulings moving away from the current industry conditions due largely to the rapid changes in technology. As to the consistency between the authorities, the study finds significant agreement, but with differences within interpretations of more complex cases. Finally, the rulings appear to be still very tied to the regulations of the regulatory agency, despite continued questioning from the antitrust authority. This indicates the necessity of a revision of the legal framework and, to some extent, of the institutional model of analysis of antitrust cases.